2013
DOI: 10.2478/folmed-2013-0004
|View full text |Cite
|
Sign up to set email alerts
|

Radial Shock Wave Therapy for Plantar Fasciitis: A One Year Follow-Up Study / Радиальная ударно-волновая терапия при подошвенном фасциите; прослеживание в течение года

Abstract: Based on the results of this study we could conclude that radial shock wave therapy is a safe non-invasive method of treatment. Our preliminary findings indicate that it could be an effective treatment of choice for patients with chronic plantar fasciitis that is recalcitrant to other conservative treatment modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…When looking specifically at rESWT though, there is still some debate as to its efficacy. Whilst many studies have found rESWT highly beneficial and conclude it to be a creditable treatment option [ 18 , 32 – 34 ], others suggest no better results than the other established therapies [ 19 , 35 37 ] or not different from placebo [ 38 ]. A recent systematic review and meta-analysis concluded that “the efficacy of low-intensity ESWT is worthy of recognition” [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When looking specifically at rESWT though, there is still some debate as to its efficacy. Whilst many studies have found rESWT highly beneficial and conclude it to be a creditable treatment option [ 18 , 32 – 34 ], others suggest no better results than the other established therapies [ 19 , 35 37 ] or not different from placebo [ 38 ]. A recent systematic review and meta-analysis concluded that “the efficacy of low-intensity ESWT is worthy of recognition” [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Storz Medical Masterpuls rESWT machine used in this study suggests the following for PF: 3–5 sessions, 2.0–3.0 bar, 3000–3500 impulses, and 12–15 Hz frequency [ 41 ]. Variations of programmes, differentiating from device instructions, have been applied in similar cases as well [ 19 , 32 , 34 , 42 ]. These variations in protocols could therefore account for the differences found, the opinions expressed in research studies suggesting that rESWT was no better than physiotherapy [ 36 , 37 ], opposite to those conveyed by others who found rESWT to be a valuable treatment modality for PF [ 18 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The AOFAS clinical rating system consists of subjective and objective variables, the objective clinical component is scored by the physiotherapist and the subjective questions are answered by the patient. A complete description of the AOFAS clinical rating scales and scoring methodology has been previously reported and indicative of the clinical rating scales' ability to discriminate and predict the quality of life related to foot and ankle conditions [8,9]. And the validity and reliability study was conducted for AOFAS [13].…”
Section: Outcome Evaluationmentioning
confidence: 99%
“…Extracorporeal shock wave therapy (ESWT) has been proposed as a potential method of treating patients with chronic diseases without the need to prevent weight-bearing [5]. Several controlled trials of ESWT for chronic PF have been published demonstrating favorable results in the range of 50% to 70% of patients after a followup period of three months after treatment [3,[6][7][8][9]. Besides, a recent study demonstrated the safety and efficacy of radial extracorporeal shock wave therapy (rESWT) for chronic PF [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation